Analysis and prediction of injected parts by using mould filling simulation software - Nurul Farhanah, Rosli (2013)
Nowadays, plastic products play an important role in human daily life and injection molding was one of the methods that can produce plastic products. By using the simulation software, the best solution to overcome problems and defects occur in plastic injection molding process can be determined. Previously, the engineers need to use the traditional method to setup new mold which is 'trial and error method'. This method need the maximum time consumption for mold setup but it was applied to make sure the outcome of the product is the best and fulfill their products requirement. Therefore, this project was conducted to analyze the melt flow behavior of injection molding process using Moldflow software and to compare the prediction outcome from Mold Flow software and actual injection molding process in term of molding defects and injection molding parameters. Then, the project was continued with the fabrication of mold until the injection of the product is produced by using NISSEI injection molding machine. After that, the actual injected part was compared with the part from the simulation. From the project result, the filling pattern of the material from both of the simulation and actual injected product is similar and the result for molding defect such as sink marks also shows similarities. As the conclusion, the utilization of the simulation software is helpful in industries because engineers and designers can predict the possibilities of the defects before the mold is built.